CO-OPERATIVE INSURANCE IN LAGOS STATE, NIGERIA: CHALLENGES AND ISSUES (Journal of the Management Sciences, 2025)
Insurance is a mechanism through which members of the society channel their resources into a pool in order to address the impact of perils that could cause devastating losses to them. Insurance per se is a form of cooperative for pooling of funds for the purposes of indemnifying losses. This study aimed at reviewing the operations of the cooperative insurance model by looking at their challenges, and benefits to the public. This study involved the use of primary data collected from respondents who are staff of co-operative insurance societies operating in Nigeria. A total of 150 copies of questionnaires were administered to the respondents from the 3000 cooperative societies in Lagos State, Nigeria. The descriptive survey research design was used in carrying out this study. The Statistical Package for Social Sciences (SPSS) was used in the test of hypotheses using Chi-square as a tool. The findings showed that there have been few studies on cooperative insurance society in Nigeria as compared to what is tenable in countries like Japan or Sri Lanka. However, this study also found that irrespective of the lower capital base of the cooperative insurance society in Nigeria, these societies provide cover for high-risk perils such as in motor insurance and more so as they do not have reinsurance protection for such covers. Cooperative insurance society could be used as a vehicle for increasing insurance penetration in Nigeria, but there is need for a review of the general operational guidelines for them.
Keywords: Cooperatives; Insurance; Challenges; Inclusion; Nigeria